Implementing Webquests Technique to Improve Students’ Reading Comprehension - Anggry Arbryan (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
The objectives of this research are: (1) to find out whether and to what extent WebQuestsTechnique improves students’ reading comprehension (2) to describe the class climatewhen WebQuests Technique applied in reading class. The research data were collected byusing techniques of observation, interview, field note, photographs, and test (pre-test andpost-test). Related to the purposes of the study, the research design used in this study wasaction research. The research findings show that the implementation of WebQueststechnique could improve students’ reading comprehension and class climate of readingclass. The research results also indicated that these Web-based learning activities couldmake students more engaged in the learning process.Keywords: Reading; WebQuests; Reading Class; Class Climate; Web-based